Fostering transformation and growth in Niger's agricultural sector - Wouterse, Fleur; Badiane, Ousmane (Wageningen Academic Publishers, 2018)
For Niger, the development of agriculture is essential to strategies to raise incomes and eradicate poverty in a sustainable manner, without further depleting its natural resource base. While traditional approaches to agricultural development have emphasized food security and have been rather technology focused, African countries are increasingly emphasizing the role of innovation in development. 'Fostering transformation and growth in Niger's agricultural sector' seeks to further the understanding of potential innovations that can sustainably transform the agriculture sector in Niger. This publication uses the agricultural value chain perspective to provide a reference point for improvements in supporting services and the business environment. The first part describes several innovations that could contribute to enhancing agricultural productivity. Particularly interesting is the emphasis on the grassroots nature of some of these innovations. The second part offers a reference point for improvements in supporting services, the business and institutional environments that can contribute to pro-poor initiatives and to a stronger linkage of smallholders to markets. The comprehensive approach taken in this book ensures its contribution to an understanding of transformative innovations in agriculture as well as enabling conditions